Utilization of Corn Flour (Zea mays L.) as Material Subtitution for Ice Cream Cone - Rismawati, Devi; Pulungan, Maimunah Hindun; Rahmah, Nur Lailatul (University of Brawijaya, 2020)
Flour needs that continue to increase will have an impact on increasing the need for flour in Indonesia. To reduce this increase, wheat flour substitution is needed. This study aims to determine the right amount of corn flour substitution for wheat flour which produces the best quality for physical properties (rendement, the thickness, the breakability, the endurance of cone to ice cream) and chemical properties (moisture content, protein content, reducing sugars) and knowing consumer acceptance of cone produced. The study was made using Factorial RandomizedÂ BlockÂ Design (FRBD) with two factors. The first factor is the proportion of corn flour and wheat flour has 5 levels (0%: 100%, 25%: 75%, 50%: 50%, 75%: 25%, 100%: 0%). The second factor is the roasting time with 3 levels (20 minutes, 25 minutes, 30 minutes). Parameters observed included water content, protein content, reducing sugar, rendement, the thickness, the breakability, the endurance of cone to ice cream and organoleptic properties such as color, aroma, texture, taste. Data obtained from physical and chemical tests were analyzed using variance (ANOVA). The results analysis of variance have significant differences so that the Smallest Significant Difference Test (LSD) is performed with a real level of 5%. Then the best selection was made from each treatment. The best selection results obtained in the treatment of 100% corn flour and 0% wheat flour with a time of 30 minutes has a moisture content of 3.52%, protein content 0,0007%, reducing sugar 0,0007%, yield 85,13%, thickness 2, 71 mm, fracture 0.26 N and cone resistance to ice cream 68 minutes 5 seconds.Keywords: Cone, Consumer Acceptance, Corn Flour, Corn